PENGARUH KINERJA KEUANGAN, KEBIJAKAN DIVIDEN, MANAJEMEN RISIKO, DAN CORPORATE GOVERNANCE TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN SEKTOR TRANSPORTASI DAN LOGISTIK YANG TERDAFTAR DI BEI TAHUN 2019-2023 - Jennifer Ong; Wirda Lilia; Jesslyn Devistania; Jessica Benedict Lauren; Julienda Br Harahap (Journal of Economic, Bussines and Accounting (COSTING), 2025)
This study aims to determine the effect of financial performance, dividend policy, risk management, and corporate governance on company value in transportation and logistics sector companies listed on the indonesia stock exchange for the 2019 – 2023 periode. The method of this study uses a quantitative approach by analyzing secondary data. The population of this study were companies listed on the IDX with a total of 10 companies, and used a purposive sampling technique. The results of this study stare that there is a partially significant effect dividend policy on company value, and there is a partially insignificant effect between financial performance, risk management and corporate governance on company value. Then, the simultaneous financial performance, dividend policy, risk management, and corporate governance have a significant effect on the company’s value.. Keywords: Procurement, Building Planning, Life Cycle Costing